E-LEARNING APPLICATION WITH MACHINE LEARNING - Saif M. Duhaim (Journal Park Publishing, 2024)
Machine learning has entered many fields, one of which is e-learning. E-learning has many applications that depend on it. These applications were designed and based on machine learning algorithms. This study surveyed the most critical applications based, designed, or created on machine learning algorithms' principles. Also highlighted are platforms that have more tools empowered by machine learning, like chatbots, recommendation engines, and adaptive quizzes.
Keywords: e-learning, machine learning, platforms